Off-Shoring and Wage Inequality: where do we stand? - Syeda Tamkeen Fatima (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2014)
The distributional impact of globalization is of great academic interest. This paper traces the progression of theoretical trade models and their ability to explain the differential impact of off-shoring on skill premiums (i.e. skilled-unskilled wage dispersion) in the recipient developing countries. In light of the increasing trend of off-shoring activities, it is important to look at its consequence on labor demand and skill composition in the south which can in turn affect the wage dispersion in these economies. The varied impact of off-shoring activities onto the wage dispersion in the south as supported by the empirical evidence calls for a comprehensive model that can reconcile these differences. The class of theoretical models pointing in only one direction of either an increase, decrease or no change in wage dispersion need to be enriched to take account of multiple equilibrium or asymmetric pattern of skill premium obtained under different circumstances.
Keywords: F16; F66; J31; 330; Off-shoring; Foreign direct investment; FDI; Wage inequality; Skill premium; Developing south; Auslandsverlagerung; Auslandsinvestition; Lohnstruktur; Qualifikation; Außenwirtschaftstheorie